Use of power method for identification of nonlinearity parameters - Zagirnyak, M.; Mosiundz, D.; Rodkin, D. (Технічна електродинаміка, 2017)
Procedure of calculation of nonlinearity parameters by power method based on equations of balance of the source and consumer instantaneous powers components according to each separate harmonic is proposed. It is demonstrated that such an approach makes it possible to obtain the required number of equations for determination of the nonlinearity parameters. The method is verified using the example of calculation of parameters of a simple electric circuit with a nonlinear inductance. Предложена методика расчета параметров нелинейностей энергетическим методом, в основе которого лежат уравнения баланса составляющих мгновенной мощности источника и потребителя по каждой отдельной гармонике. Показано, что такой подход позволяет получить необходимое количество уравнений для определения параметров нелинейностей. Методика проверена на примере расчета параметров простейшей электрической цепи с нелинейной индуктивностью. Запропоновано методику розрахунку параметрів нелінійностей енергетичним методом, в основі якого лежать рівняння балансу складових миттєвої потужності джерела і споживача за кожною окремою гармонікою. Показано, що такий підхід дозволяє отримати необхідну кількість рівнянь для визначення параметрів нелінійностей. Методика перевірена на прикладі розрахунку параметрів найпростішого електричного кола з нелінійною індуктивністю.